Eksperimen Pembelajaran Matematika Melalui Problem Based Learning Dan Problem Solving Learning Ditinjau Dari Aktivitas Siswa Terhadap Prestasi Belajar(Pada Siswa Kelas VII SMP Negeri 2 Colomadu Tahun Ajaran 2015/2016) - KASARI MUCHLISIN, DEVI, Dr. Sumardi, M.Si (2016)
The purpose of research to describe and analyze: (1) the effect of mathematics learning with Problem Based Learning (PBL) and Problem Solving Learning (PSL) based to mathematics achievement, (2) the effect of learn activity connection to mathematics achievement, (3) the interaction between learning strategy and learn activity connection to mathematics achievement. The type of the research is experiment with quasi experimental design. The population of the research was all students of VII Grade of SMP N 2 Colomadu of odd semester of academic year 2015/2016. The research sample consisted of two classes. The sampling technique use cluster random sampling. Methods of data collection use test and documentation. Data analyzed by analysis of variance with two different cell lines. The results of data analysis with a significance level of 5% was obtained: (1) there is effect of Problem Based Learning (PBL) and Problem Solving Learning (PSL) based to mathematics achievement, with FA=11,254 (2) there is effect of student's mathematical connection for mathematics achievement, with FB = 95,877 (3) there is no interaction between Problem Based Learning (PBL) and Problem Solving Learning (PSL) based with learn activity connection to mathematics achievement, with FAB = 2,955